Collective bargaining and minimum wage determination in Nigeria - Omolabi, Issa; Salman, Abdulrasaq; Ishola, Abdulrasaq Ajadi; Abdulkareem, Abdulrazaq Kayode (Penerbit Universiti Kebangsaan Malaysia, 2021)
Wage is central and critical to employees as oxygen is to life. Of all personnel problems, paying employees is perhaps the most perplexing one. It involves many emotional factors. The essence of wage determination is to guarantee workers the necessary psychological support required for better performance. In Nigeria, those with jobs could not effectively cover their expenses as their take-home pay cannot take them anywhere. The conditions of service kept going down. In addressing the wage and expenses imbalances, collective bargaining emerged. This study thus examined the effect of collective bargaining on minimum wage determination in Nigeria. The study targeted employees of both state and federal government establishments in the South-West geo-political zone. The sample size for the study was 600 employees of both state and federal government. The study found that the prerequisite factors relevant for consideration during wage negotiation has been ignored and thus impaired effective wage standard. The study concluded that the increasing cost of living has not been in correspondence with the minimum wage paid by the government. Hence, employees were demotivated with their pay. It thus became necessary that collective bargaining be resulted to facilitate the required increase in their pay wage. The paper recommended periodic interactive sessions with the unions to regularly meet to monitor wages and salaries trends and cognisance of inflation trends.